2018
DOI: 10.1371/journal.pone.0208485
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between iron deficiency anemia and sexual function and satisfaction among reproductive-aged Iranian women

Abstract: Iron deficiency anemia (IDA) is a common micronutrient deficiency worldwide, and an important health problem especially in women of reproductive age. This study aimed to determine the relationship between IDA and sexual satisfaction and function among reproductive-aged Iranian women. In this study, 129 women (52 with IDA and 77 non-IDA) with age 18–45 in Mahshahr, Iran were recruited. Data was gathered by a demographic questionnaire, Female Sexual Function Index (FSFI) and Larson Sexual Satisfaction Questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…It is well established that iron-deficiency anemia (IDA) leads to fatigue, anxiety, weakness, and impaired physical and mental capacity [ 34 ]. For these reasons, IDA is thought to be a significant factor reducing sexual function in women [ 35 ]. Gulmez et al [ 36 ] showed that iron supplementation in 207 women with IDA significantly enhanced sexual performance score as well as improved physical and social function while decreasing anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that iron-deficiency anemia (IDA) leads to fatigue, anxiety, weakness, and impaired physical and mental capacity [ 34 ]. For these reasons, IDA is thought to be a significant factor reducing sexual function in women [ 35 ]. Gulmez et al [ 36 ] showed that iron supplementation in 207 women with IDA significantly enhanced sexual performance score as well as improved physical and social function while decreasing anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…[74][75][76][77][78][79] Finally, deficiencies in Vitamin D and iron are linked to sexual dysfunction, with improvement seen after repletion. [80][81][82][83] Sedentary lifestyle increases the risk of sexual dysfunction through its impact on lifestyle-related chronic disease risk, mood, and body image. [84][85][86][87][88][89][90] Conversely, regular physical activity is associated with higher sexual desire, more frequent sexual activity, and lower risk of sexual dysfunction in women.…”
Section: Sexual Healthmentioning
confidence: 99%
“…74-79 Finally, deficiencies in Vitamin D and iron are linked to sexual dysfunction, with improvement seen after repletion. 80-83…”
Section: Sexual Healthmentioning
confidence: 99%
“…Meanwhile, evidence suggests that vitamin D and iron deficiencies are risk factors for sexual dysfunction, and resolution of these deficiencies may well be therapeutic. 55-58 Vitamin D receptors exist on the uterus and ovaries, where they can influence steroidogenesis and testosterone aromatization, with consequent effects on sex hormone levels. 59-61 In iron-deficiency anemia, fatigue is thought to mediate the relationship between deficiency and sexual dysfunction.…”
Section: Sexual Healthmentioning
confidence: 99%
“…59-61 In iron-deficiency anemia, fatigue is thought to mediate the relationship between deficiency and sexual dysfunction. 57 Testing for vitamin D and iron deficiency may be considered as a relatively simple and low-cost addition to the workup for female sexual dysfunction.…”
Section: Sexual Healthmentioning
confidence: 99%